Gender and Citizenship in the Middle East - Safoi Babana-Hampton (American Journal of Islam and Society, 2001)
The fourteen case studies that compose this volume address the various institutional, economic, social, cultural, and political dimensions of the debate on gender and citizenship in the Middle East. Using a crosscultural comparative approach, the theoretical introduction as well as the individual case studies seek to challenge dominant (especially western) feminist models of analysis of the question of gender and citizenship in the Middle East. The validity of dominant feminist paradigms is questioned by introducing new social and cultural variables, and putting at stake a number of traditionally unquestioned or unrecognized modes of identity formation, such as kinship, family, tribe, and sects, which critically affect a woman's citizenship status. The volume purports to contest essentializing myths about the Middle East that artificially give it a character of regional coherence, and homogenize the image of Middle Eastern women as a category. The volume thus theorizes the gendering of citizenship from the largely unexplored perspectives that open up from introducing the above variables, toward a better understanding of the complex nature of the laws (religious, political, patriarchal and patrilineal) governing the construction of a gendered citizenship in the Middle East. The theoretical introduction to the volume outlines the dynamics of a number of points of departure that presumably underlie the writing of the "legal subject in the Middle East," namely nations, states, religion, family. The contributors seem to all concede that "most Middle Eastern states have cemented the linkage between religious identity, political identity, patrilineality, and patriarchy-that is, between religion, nation, state, and kinship." The Middle Eastern countries studied in the volume are divided regionally into four areas: North Africa (including Egypt, Algeria, Tunisia and Morocco); Eastern Arab States (including Lebanon, Palestine, Jordan and Iraq); the Arab Gulf (including Saudi Arabia, Kuwait and Yemen); the Non-Arab Middle East (including Turkey, Iran, and Jewish and Palestinian Arab women in Israel). The authors of the various case studies conducted an exhaustive investigation of the related topics, albeit with a notable difference of outlook varying between liberal individualistic and communitarian conservative positions. The methodological approach adopted by various contributors draws ...